6 Effect of an EMS body-worn camera. (26th April 2019) - Ho, JD; Hick, JL; Nystrom, PC; Simpson, NS; Jones, GA; Miner, JR
Abstract : Background: Body-Worn Cameras (BWCs) are not widely used in EMS. Preliminary study demonstrates a BWC effect on EMS performance. We hypothesize that there are other benefits yet to be discovered. We seek to identify other effects BWCs may have. Method: This is a 30 day observation study of 20 EMS providers wearing BWCs during duty shifts in February, 2018. Metrics tracked were citizen and employee complaints and comments related to the BWC, complaint investigation, and EMS personnel feedback and education related to BWC use. Results: There were no formal complaints made by citizens or employees related to BWC use. There were several neutral to positive comments made related to enhanced accuracy and transparency. There were 6 incidents that involved BWC footage requiring investigatory review. BWC immediate feedback allowed investigation closure within a few hours. In multiple cases, the BWC sparked meaningful discussion between EMS and the patient or their family. In at least 1 instance, there was de-escalation of an agitated bystander when the BWC was noticed. Conclusion: EMS use of BWCs encourages transparency, accuracy, and immediate feedback to EMS personnel. They are helpful in timely complaint resolution and continuing education. Their use appears to be well-received by the public and shows promise in de-escalating some agitated persons. We encourage more study of how BWCs can improve EMS patient care. Reference: Ho JD, Dawes DM, McKay EM, Taliercio JJ, White SD, Woodbury BJ, Sandefur MA and JR Miner. Effect of Body-Worn Cameras on EMS Documentation Accuracy: A Pilot Study. Prehosp Emerg Care 2017;21:263–271. Conflict of interest: JD Ho serves as the medical director to Axon Enterprise, Inc. (manufacturer of body worn cameras) and owns stock in this company. Axon Enterprises supplied the cameras utilized in this study. Funding: Axon Enterprise, Inc. provided the cameras utilized in this study free of charge.